The Community-based Character Education: Study of the 'Imaji Academy' Program in Madrasa - Hairul Huda; Siti Nursyamsiyah; Mochamad Alfan (Indonesian Journal of Islamic Education Studies (IJIES), 2022)
This study aims to describe the implementation of the Imaji Academy program as strengthening student character education. The research method used descriptive qualitative. Research data collection was done through interviews, observation, and documentation. Data analysis in this study followed three stages: data condensation, data presentation, and verification. The results of this study found that the Imaji Academy program at MI Darussalam 02 Jember is manifested in three feature classes, namely, literacy feature class, sociopreneur feature class, and cultural arts feature class. Meanwhile, the agricultural class has been formulated but has not been implemented. Dominant character values ​​of the three feature classes consist of religious, gotong royong, and cultural arts values that strengthen students' character. The indicator was several works produced by students collectively. Based on the study's results, the researcher suggests strengthening the implementation of feature classes, mainly feature classes that have not been implemented. This study also suggests the importance of schools building collaboration with the community to strengthen student character education sustainably.